Bactericidal activities of new beta-lactam antibiotics against Bacteroides fragilis. - Yu, P K (1983)
The bactericidal activities of cefoxitin, cefoperazone, cefotaxime, moxalactam, mezlocillin, and piperacillin were determined in duplicate against low and high inocula of each of 10 Bacteroides fragilis strains. Antibiotic concentrations resulting in 99.9% killing were established by quantitation of the inocula just before anaerobic incubation of tests and by subcultures of volumes sufficient to accurately determine less than or equal to 0.1% survivors. Inoculum effects on inhibitory and bactericidal activities were least for cefoxitin and greatest for cefoperazone and cefotaxime. Bactericidal-to-inhibitory concentration ratios of greater than or equal to 8 occurred most frequently with mezlocillin and piperacillin, regardless of inoculum size; however, 55% of the strains tested at the low inoculum size and 38% of those tested at the high inoculum size against the six antibiotics had bactericidal-to-inhibitory concentration ratios of greater than or equal to 4.